Ammonium phosphomolybdate composite silane modified polyacrylonitrile material, preparation method thereof and application of ammonium phosphomolybdate composite silane modified polyacrylonitrile material in cesium adsorption

By embedding ammonium phosphomolybdate in polyacrylonitrile and modifying with silane coupling agent, an efficient ammonium phosphomolybdate composite silane modified polyacrylonitrile material is solved, and the small amount of cesium adsorption and non-recyclable utilization in the prior art is solved. The problem of this problem has achieved efficient and reusable cesium adsorption effect and good thermal stability.

CN119236895APending Publication Date: 2025-01-03YANTAI HUICUI INTELLIGENT ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411451253.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, ammonium phosphomolybdate, as a cesium adsorption material, has problems such as small adsorption amount, poor stability and unrecyclable, resulting in poor effect in removing the radioactive contaminant cesium.

Method used

Using ammonium phosphomolybdate composite silane modified polyacrylonitrile material, by embedding ammonium phosphomolybdate in polyacrylonitrile, the porous structure of the material is improved by using silane coupling agent, and its ion exchange performance is improved, forming an efficient and repeatable Adsorbents used.

Benefits of technology

It has achieved efficient adsorption and reusability of cesium, with an adsorption amount of 81.7 mg·g-1 and above, and spontaneous adsorption of cesium at room temperature, and has good thermal stability and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236895A_ABST
    Figure CN119236895A_ABST
Patent Text Reader

Abstract

The invention discloses an ammonium phosphomolybdate composite silane modified polyacrylonitrile material as well as a preparation method and application thereof in cesium adsorption. The invention belongs to the field of nuclear industry wastewater purification treatment. The technical problems that a purification material is poor in cesium adsorption effect, difficult to recycle and the like are solved. According to the ammonium phosphomolybdate composite silane modified polyacrylonitrile material prepared by the invention, the polyacrylonitrile material is modified by using a silane coupling agent, and then the ammonium phosphomolybdate is embedded into a porous matrix of the silane modified polyacrylonitrile material by using an in-situ polymerization method, so that the adsorbability of an adsorbent to cesium is improved, and the adsorption rate of the material to cesium is improved. The method is simple in preparation process, convenient to operate, low in product raw material price and high in yield, materials for adsorbing pollutants are convenient to recycle, the adsorbed pollutants are also convenient to separate and recycle, and industrial cesium recycling is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nuclear industrial wastewater purification and treatment, and specifically relates to an ammonium phosphomolybdate composite silane-modified polyacrylonitrile material and a preparation method thereof and application thereof in cesium adsorption. Background Art

[0002] In order to meet the increasingly urgent energy demand, the nuclear industry is booming and plays a key role in the world's electricity production. At the same time, extreme weather in some regions has intensified, and clean energy such as wind and solar energy are not enough to become the main energy source in these regions. Compared with traditional fossil fuels and other alternatives, nuclear power does not emit greenhouse gases such as sulfur dioxide and carbon dioxide, which is conducive to protecting the environment and responding to climate change. It has the advantages of clean and low carbon, and nuclear power has a high fuel density. The energy generated by the complete fission of 1 kilogram of uranium-235 is approximately equivalent to 2,500 tons of coal. However, weapons testing, the use of nuclear energy and nuclear accidents have generated a large amount of nuclear waste. These radioactive wastes are released into the environment under the influence of factors such as atmospheric air currents and ocean currents, causing varying degrees of pollution to surface water and groundwater around the world.

[0003] Among various radionuclides, cesium (Cs) is one of the most harmful isotopes due to its long half-life, release of high-energy β / γ radiation, high solubility, and easy entry into the human body. Considering the urgency of removing harmful radioactive substances such as cesium, the adsorption and environmental remediation of cesium in aqueous solutions have received extensive attention. On the other hand, cesium can be used as a radiation source in agriculture, cancer treatment, coal exploration and other fields. Therefore, from the perspective of environmental society and sustainable development of nuclear power, cesium is a double-edged sword. Therefore, the recovery of cesium in wastewater and radioactive waste is urgent.

[0004] Ammonium phosphomolybdate (AMP) is a yellow crystalline inorganic compound that can be used as an inorganic ion exchanger with high adsorption capacity and selectivity for cesium. Most of the existing technologies for adsorbing cesium directly place fine powdered AMP in a cesium-containing solution. The fine powdered AMP is very easy to leak in the solution, which not only weakens the adsorption of the material, but also causes waste of resources. Therefore, in view of the technical problems such as poor adsorption effect of existing purification materials on cesium and difficulty in recycling, it is urgent to develop an AMP material with large cesium adsorption capacity, good stability and good repeatability to achieve efficient selective adsorption and recovery of radioactive pollutant cesium. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of small adsorption capacity, poor stability and non-recyclability of cesium absorbing materials. The present invention provides an ammonium phosphomolybdate composite silane modified polyacrylonitrile material and a preparation method thereof and an application thereof in cesium adsorption.

[0006] The technical solution of the present invention is as follows:

[0007] One of the purposes of the present invention is to provide an ammonium phosphomolybdate composite silane-modified polyacrylonitrile material, wherein the modified polyacrylonitrile material is prepared from AMP, a silane coupling agent and polyacrylonitrile (PAN).

[0008] It is further defined that the mass ratio of AMP, silane coupling agent and PAN is 2.5:0.1-0.75:2.5.

[0009] It is further defined that the silane coupling agent is 3-aminopropyltriethoxysilane or γ-glycidyloxypropyltrimethoxysilane.

[0010] The second object of the present invention is to provide a method for preparing an ammonium phosphomolybdate composite silane-modified polyacrylonitrile material, the method comprising:

[0011] Step 1: First drop Tween 80 into the dimethyl sulfoxide solution, then add AMP and stir evenly;

[0012] Step 2: Add PAN and silane coupling agent to the above solution, stir evenly, and drop into deionized water to obtain ammonium phosphomolybdate composite silane modified polyacrylonitrile (AMP-PAN-Si) material.

[0013] It is further defined that in step one, the volume ratio of the dimethyl sulfoxide solution in step one to Tween 80 is 10-50 mL: 0.1-1 g.

[0014] It is further defined that the reaction temperature in step 1 is 30-80°C.

[0015] It is further defined that in step 1, the stirring speed is 150-500 rpm and the stirring time is 0.5-2 h.

[0016] It is further defined that the reaction temperature in step 2 is 30-80°C.

[0017] It is further defined that in step 2, the stirring speed is 500-2000 rpm and the stirring time is 0.5-10 h.

[0018] The third object of the present invention is to provide an application of ammonium phosphomolybdate composite silane modified polyacrylonitrile material in adsorbing cesium.

[0019] Compared with the existing technology, the specific advantages are as follows:

[0020] (1) The present invention uses AMP as the main cesium adsorption material, uses PAN-Si as the base material to load AMP, and uses the in-situ polymerization method to embed AMP into the PAN-Si porous matrix to improve the shortcomings of the fine powder form of AMP powder, optimize the adsorption performance of AMP ion exchange, improve the adsorption of cesium by the adsorbent, and increase the adsorption rate of the material to cesium.

[0021] (2) The preparation process of the present invention is simple and easy to operate. The raw material price of the product is low and the output is large. The material for adsorbing pollutants is easy to recover, and the adsorbed pollutants are also easy to separate and recover, which is convenient for the recycling of cesium elements.

[0022] (3) The material of the present invention has a high adsorption capacity for cesium, and at the same time has high reusability and thermal stability, does not generate secondary waste, and is environmentally friendly. The high-efficiency ammonium phosphomolybdate composite silane-modified polyacrylonitrile material prepared by the present invention can spontaneously adsorb cesium at room temperature, and the maximum adsorption amount can reach 81.7 mg·g -1 And above. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The material morphology diagrams of Examples 1-3 and Comparative Example 1 are shown;

[0024] Figure 2 a is the infrared spectrum of PAN powder obtained in Example 1; Figure 2 b is the infrared spectrum of the AMP-PAN-Si material obtained in Example 1;

[0025] Figure 3 The XPS spectra of the AMP-PAN-Si material obtained in Example 1 (a is the full spectrum; b is the C1s spectrum; c is the O1s spectrum; d is the Mo3d spectrum;

[0026] Figure 4 The N2 atmosphere adsorption-desorption isotherm and pore size distribution diagram of AMP-PAN-Si obtained in Example 1;

[0027] Figure 5 The morphology of the AMP-PAN-Si material obtained in Example 1 before and after the adsorption of cesium: (a). Morphology of AMP-PAN-Si material; (b). Morphology of AMP-PAN-Si-Cs material; (c). Distribution of Cs elements on AMP-PAN-Si-Cs material; (d). Element distribution of Mo, O, P, C, N, and Si on AMP-PAN-Si-Cs; (e). EDS spectrum of AMP-PAN-Si material; (f). EDS spectrum of AMP-PAN-Si-Cs material;

[0028] Figure 6 This is a graph showing the change in cesium adsorption capacity of the AMP-PAN-Si material prepared in Example 1 as a function of pH;

[0029] Figure 7 The desorption effect of AMP-PAN-Si prepared in Example 1 under different types and concentrations of desorbents;

[0030] Figure 8This is the thermogravimetric analysis diagram of the AMP-PAN-Si material obtained in Example 1. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing an ammonium phosphomolybdate composite silane-modified polyacrylonitrile material, which is achieved by the following steps:

[0032] (1) Add 2-10 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O) is dissolved in 10-100 mL of deionized water and stirred until dissolved to obtain solution A. 1-10 mL of concentrated nitric acid is added to 10-100 mL of deionized water, and then 1-5 g of potassium pyrophosphate (K4P2O7·3H2O) is added to obtain solution B. Solution B is slowly dripped into solution A and aged for 24-48 h to obtain precipitate C. The precipitate C is washed, filtered and dried to obtain yellow powdery precipitate AMP.

[0033] (2) First, drop 0.1-1 g of Tween 80 into 10-50 mL of dimethyl sulfoxide solution, then add 2.5 g of the above AMP, and stir evenly; add 2.5 g of polyacrylonitrile and 0.1-0.75 g of silane coupling agent to the above solution, stir evenly, drop into deionized water, wash and dry, and obtain AMP-PAN-Si material.

[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0036] Embodiment 1:

[0037] (1) 6.72 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O) was dissolved in 40mL of deionized water and stirred until dissolved to obtain solution A. 5mL of concentrated nitric acid was added to 35mL of deionized water, and then 2g of potassium pyrophosphate (K4P2O7·3H2O) was added to obtain solution B. Solution B was slowly dripped into solution A and aged for 24h to obtain precipitate C. First, 1mol·L -1 Wash with nitric acid, filter, and then use deionized water to make the solution neutral. Dry at 50℃ for 10 minutes to obtain yellow powdery precipitate AMP.

[0038] (2) First, 0.2 g of Tween 80 was dripped into 25 mL of dimethyl sulfoxide solution, and then 2.5 g of the above AMP was added, and the mixture was stirred at 50 ° C and 250 rpm for 1 h; 2.5 g of PAN and 0.5 g of APTES were added to the above solution, and the mixture was stirred at 50 ° C and 1000 rpm for 5 h, and then deionized water was dripped into the solution, and the mixture was washed three times with deionized water, and dried at 60 ° C for 24 h to obtain AMP-PAN-Si material.

[0039] Embodiment 2:

[0040] The steps were the same as in Example 1, except that the amount of APTES added was 0.25 g.

[0041] Embodiment 3:

[0042] The steps were the same as in Example 1, except that the amount of APTES added was 0.75 g.

[0043] Comparative Example 1:

[0044] The steps were the same as in Example 1, except that the amount of APTES added was 1.0 g.

[0045] Static adsorption experiment:

[0046] Dissolve non-radioactive cesium chloride (CsCl) in deionized water to prepare standard Cs + Solution (1000mg·L -1 ), which can be diluted to a solution of a specified concentration for further experiments. The pH of the solution was adjusted with 0.1 mol / L HCl and NaOH solutions and measured with a pH meter. The adsorption was carried out in a horizontal constant temperature oscillator, with 3 parallel samples set up in each group. After constant temperature oscillation, the samples were filtered with a 0.45 μm filter membrane, and the Cs in the adsorbed solution was determined by inductively coupled plasma atomic emission spectrometry (ICP). + Concentration. Material to Cs + The adsorption capacity was calculated by the following formula:

[0047]

[0048] Where: q e is the adsorption capacity (mg·g -1 ), η is the adsorption rate. C0 and C e Cs at initial and equilibrium + Liquid phase concentration (mg·L -1 ); m is the amount of adsorbent added (g); V is the volume of the solution (L).

[0049] Desorption performance experiment:

[0050] In order to obtain adsorption materials with excellent adsorption and desorption cycle performance, it is necessary to select a suitable desorbent to ensure the reusability of the material. Desorption experiments were carried out using H2O, KCl, and NH4Cl solutions as desorbents. -1 50 mL of cesium solution was transferred to a conical flask and adsorbed with adsorbent material. The desorption time was 1 day. After the experiment, the material was taken out to test the cesium concentration C2 (mg·L -1 ). The calculation formula of the desorption rate γ (%) is as follows.

[0051]

[0052] Analysis of adsorption-desorption isotherms and pore size distribution:

[0053] The basic equation for calculating specific surface area from adsorption data is:

[0054]

[0055] Where, X m is the mass of the adsorbate forming a single layer on the unit mass of the adsorbent, M is the molecular weight of the adsorbate, and A m is the area occupied by a single adsorbate molecule in the monolayer, and N is the Avogadro number.

[0056] Table 1 Morphology and adsorption properties of AMP-PAN-Si materials in Examples 1-3 and Comparative Example 1

[0057] Serial number <![CDATA[Maximum adsorption capacity / mg·g -1 > Example 1 81.7 Example 2 75.6 Example 3 65.7 Comparative Example 1 45.1

[0058] Table 2 Thermodynamic parameters of cesium adsorption on AMP-PAN-Si materials

[0059]

[0060] Table 2 shows the Gibbs free energy (ΔG o / kJ·mol -1 ), the enthalpy change of the reaction (ΔH o / kJ·mol -1 ) and the entropy change of the reaction (ΔS o / kJ·mol -1 ·K -1 ). The Gibbs free energy ΔG calculated according to the formula ΔG=ΔH-TΔS o is negative, indicating that the adsorption process is spontaneous; enthalpy change ΔH o and entropy change ΔS o are all positive, indicating that AMP-PAN-Si material adsorbs Cs + The process is endothermic and spontaneous, which proves that the material prepared in this application can spontaneously adsorb Cs without adding any additional additives.+ .

[0061] Figure 1 These are appearance pictures of Examples 1-3 and Comparative Example 1. It can be seen from the pictures that when the amount of APTES exceeds 0.75 g, the materials become sticky.

[0062] Figure 2 This is the infrared spectrum of the AMP-PAN-Si material in Example 1. From the FTIR results, it can be seen that at 2240.6 cm -1 The spectrum at 960.2cm belongs to -C≡N in PAN material. The spectrum region belonging to the Keggin structure of AMP is: -1 、860.1cm -1 and 792.6cm -1 , which belong to the absorption peaks of corner-sharing and edge-sharing octahedra of Mo-O bonds and Mo-O-Mo bonds respectively; 1063.4cm -1 The characteristic peak belongs to the PO bond. 1390cm -1 ~1500cm -1 The peaks in the range belong to NH4 + .799cm -1 The characteristic peak at 1093 cm is the symmetric stretching vibration of Si-O bond. -1 At 3300cm -1 ~3600cm -1 The broad absorption peak observed in the range is the stretching vibration of the hydroxyl group. As can be seen from the figure, ammonium phosphomolybdate and silane groups exist in the synthesized material, while the Keggin structure of the AMP material is retained.

[0063] Figure 3 This is the XPS spectrum of the AMP-PAN-Si material in Example 1. Figure 3 (a) is a full scan of the material, showing a small Si atom peak, which proves the reaction between aminosilane and PAN. The low Si content indicates that the reaction efficiency between the -NH2 group in aminosilane and the -C=N group in PAN is low. Figure 3 (b) is the peak spectrum of the C element. The peaks at the binding energy of 284.8 eV and 285.7 eV belong to CC(H) and CC-CN respectively, and the peak at the binding energy of 288.1 eV belongs to -C=N-. Its lower peak area also proves that the degree of amination reaction is low. Figure 3 In (c), 530.8 eV is the 1s orbital binding energy of O element. Figure 3 The peaks at 231.6 eV and 234.8 eV in (d) belong to the Mo 3d 5 / 2 and Mo 3d 3 / 2The combined analysis of FTIR and XPS proves that PAN reacts with APTES to generate PAN-Si material, and AMP is successfully loaded.

[0064] Figure 4 The BET test result of Example 1 is shown in the figure. It can be seen from the figure that the average pore size of the AMP-PAN-Si material is 2.446nm and the specific surface area is 20.01m 2 ·g -1 . According to the IUPAC classification standard, the adsorption-desorption isotherm of AMP-PAN-Si adsorbent material is a type IV H (H4) hysteresis loop, indicating that its structure is composed of irregular flaky particles with narrow gaps, cracks and wedge-shaped areas. From the pore size distribution diagram, it can be concluded that the pore size distribution of the material is uneven, and the pore size is mainly distributed around 2nm-4nm, showing the characteristics of a diverse distribution of micropores and mesopores. These small pores improve the efficiency of cesium adsorption of AMP-PAN-Si adsorbent material.

[0065] Figure 5 This is a microscopic picture of the AMP-PAN-Si material in Example 1. Figure 5 a is the morphology of AMP-PAN-Si material, Figure 5 b is the morphology of AMP-PAN-Si-Cs material. Figure 5 c is the distribution of Cs element on AMP-PAN-Si-Cs material, Figure 5 d is the element distribution of Mo, O, P, C, N, and Si on AMP-PAN-Si-Cs. Figure 5 e is the EDS spectrum of AMP-PAN-Si material, Figure 5 f is the EDS spectrum of AMP-PAN-Si-Cs material. According to the obtained electron microscope image, its structure is composed of irregular flaky particles with a large number of pores and cracks. According to the Cs element distribution diagram after the material adsorbs cesium, it can be seen that the adsorption of Cs + The generated material filled the internal cracks, and the surface was smoother than that of AMP-PAN-Si material. The cesium atomic distribution of AMP-PAN-Si-Cs material was 0.5%, proving that Cs + It has been adsorbed into the material. The energy spectrum has Si peaks, and the Si element is evenly distributed on the surface of the material in the MAPPING diagram, proving that PAN and APTES react successfully and SiO2 is covalently grafted to the PAN surface. After cesium is adsorbed, due to the NH4 + With Cs + The ion exchange reaction caused the surface nitrogen content to decrease from 20.00% to 16.58%.

[0066] Figure 6The graph of the cesium adsorption capacity of the AMP-PAN-Si material of Example 1 as a function of pH shows that when the pH is low, the adsorption performance of the material decreases to a certain extent. This is due to the fact that H + and Cs + Competition for adsorption sites results in a low adsorption capacity and efficiency of the material. When the pH gradually increases to 7, H + Reduce, for Cs + The competition for adsorption also decreases, and the adsorption capacity of the material increases to a maximum value of 81.6 mg g -1 When the solution pH increases to 8-11 and becomes weakly alkaline, Cs + Still in the form of hydrated ions [Cs(H2O) n ] + The morphology is presented, but due to the introduction of NaOH to adjust the pH + Also with Cs + Competition caused the adsorption capacity to decrease. When the pH continued to increase to 12, due to the interaction between AMP and OH - The reaction structure is destroyed, resulting in a significant decrease in adsorption performance. As shown in the figure, the adsorption capacity of AMP-PAN-Si material changes with pH, ​​showing that it can adsorb Cs in a wide pH range. + , showing good acid resistance.

[0067] Figure 7 The desorption effect of AMP-PAN-Si material under different types and concentrations of desorbents in Example 1 is shown in Figure 1. The adsorption time is 48 h, the desorption time is 24 h, and the Cs + The pH of the solution is 7.0, Cs + Concentration: 100 mg·L -1 , 0.06g AMP-PAN-Si material was used in 50mL desorbent in a constant temperature shaker at 25℃ for desorption. As shown in the figure, NH4Cl has the best effect as a desorbent for AMP-PAN-Si material. When the concentration of NH4Cl is 4mol·L -1 In the case of , the desorption rate can reach up to 71.7%, and the desorption rate of KCl can reach 44.9%, indicating that K + With Cs + The ion exchange reaction is weaker than that of NH4 + . After desorption, Cs + After concentration, it can be reused. NH4Cl solution can be used as a carrier of Cs + The AMP-PAN-Si material is an effective desorption medium, and the repeatability of the AMP-PAN-Si material is good.

[0068] Figure 8This is the thermogravimetric analysis diagram of the AMP-PAN-Si material in Example 1. The configured sample to be tested was subjected to thermogravimetric testing under temperature program control of 10°C per minute. The TGA curve shows that the mass of the material gradually changes with the increase of temperature, and two different DTA exothermic peaks are presented at temperatures of approximately 303.0°C and 453.8°C. The weight loss process is mainly distributed in three regions. Before 303.0°C, the mass loss is 4.52% due to the loss of free water and adsorbed water in the AMP-PAN-Si material; between 303.0°C and 453.8°C, the mass loss is 7.62% due to the decomposition of crystal water and ammonium ions in the polymer structure; finally, after 453.8°C, the Keggin structure of AMP decomposes at high temperature to generate compounds containing phosphorus and molybdenum, resulting in a weight loss of 36.48%. The change process of the mass of the sample with temperature and time can also correspond to the components of the AMP-PAN-Si material. And the material is mainly used to adsorb Cs from the solution at room temperature. + Therefore, AMP-PAN-Si material is used for Cs in room temperature solution + It can maintain a stable structure when removed and has good thermal stability.

[0069] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. An ammonium phosphomolybdate composite silane-modified polyacrylonitrile material, characterized in that: The modified polyacrylonitrile material is prepared from ammonium phosphomolybdate, a silane coupling agent and polyacrylonitrile.

2. The modified polyacrylonitrile material according to claim 1, characterized in that: The mass ratio of ammonium phosphomolybdate, silane coupling agent and polyacrylonitrile is 2.5:0.1-0.75:2.

5.

3. The modified polyacrylonitrile material according to claim 1, characterized in that: The silane coupling agent is 3-aminopropyltriethoxysilane or γ-glycidyloxypropyltrimethoxysilane.

4. The method for preparing the ammonium phosphomolybdate composite silane-modified polyacrylonitrile material according to any one of claims 1 to 3, characterized in that: The method: Step 1: First drop Tween 80 into the dimethyl sulfoxide solution, then add ammonium phosphomolybdate and stir evenly; Step 2: Add polyacrylonitrile and silane coupling agent to the above solution, stir evenly, and drop into deionized water to obtain ammonium phosphomolybdate composite silane modified polyacrylonitrile material.

5. The preparation method according to claim 4, characterized in that: In step 1, the volume ratio of the dimethyl sulfoxide solution to Tween 80 is 10-50 mL: 0.1-1 g.

6. The preparation method according to claim 4, characterized in that: The reaction temperature in step 1 is 30-80°C.

7. The preparation method according to claim 4, characterized in that: In step 1, the stirring speed is 150-500 rpm and the stirring time is 0.5-2 h.

8. The preparation method according to claim 4, characterized in that: The reaction temperature in step 2 is 30-80°C.

9. The preparation method according to claim 4, characterized in that: In step 2, the stirring speed is 500-2000 rpm, and the stirring time is 0.5-10 h.

10. Use of the ammonium phosphomolybdate composite silane-modified polyacrylonitrile material according to any one of claims 1 to 3 in adsorbing cesium.